Dapagliflozin Ameliorates the Formation and Progression of Experimental Abdominal Aortic Aneurysms by Reducing Aortic Inflammation in Mice. (28th January 2022) - Liu, Haole; Wei, Panpan; Fu, Weilai; Xia, Congcong; Li, Yankui; Tian, Kangli; Li, Yafeng; Cheng, Daxin; Sun, Jiaying; Xu, Yangwei; Lu, Ming; Xu, Boyu; et al.
Abstract : Background . Dapagliflozin, a sodium glucose transporter protein-2 (SGLT-2) inhibitor, reduces the risk for cardiovascular diseases. However, the influence of dapagliflozin on nondissecting abdominal aortic aneurysms (AAAs) remains unclear. Methods . AAAs were created in male C57BL/6 mice via intra-aortic porcine pancreatic elastase (PPE) infusion. Mice were daily treated with dapagliflozin (1 or 5 mg/kg body weight) or an equal volume of vehicle through oral gavage beginning one day prior to PPE infusion for 14 days. To investigate its translational value, dapagliflozin or vehicle was also administered to mice with existing AAAs in another cohort. Aortic diameters were measured prior to (day 0 for baseline) and 14 days after PPE infusion. After sacrifice, mice aortae were collected, and following histological analyses were performed. Results . Dapagliflozin treatment significantly reduced aneurysmal aortic expansion following PPE infusion as compared to vehicle treatment especially at 5 mg/kg body weight (approximately 21% and 33% decreases in 1 and 5 mg/kg treatment groups, respectively). The dose-dependent attenuation of AAAs by dapagliflozin was also confirmed on histological analyses. Dapagliflozin remarkably reduced aortic accumulation of macrophages, CD4 + T cells, and B cells particularly following dapagliflozin treatment at 5 mg/kg. Dapagliflozin treatment also markedly attenuated medial SMC loss. Though the difference was not significant, dapagliflozin treatment tended to attenuate CD8 + T cells and elastin degradation. Dapagliflozin treatment at 5 mg/kg caused a 53% reduction in neovessel density. Furthermore, dapagliflozin treatment mitigated further progress of existing AAAs. Conclusion . Dapagliflozin treatment ameliorated PPE-induced AAAs by inhibiting aortic leukocytes infiltration and angiogenesis.